Nicaragua : Public Expenditure Review 2001-2006 - World Bank (Washington, DC, 2012)
Nicaragua has made impressive progress since 2001 in reducing the overall fiscal deficit. A series of internal and external shocks (hurricane Mitch, banking crisis, elections) reopened major fiscal gaps at the end of the 1990s, which threatened to destabilize the economy. Since then, fiscal management has remained prudent in spite of spending pressures, resulting in an improvement of the combined public sector balance (after grants) from a deficit of 5.4 percent of Gross Domestic Product (GDP) in 2002 to a surplus of 0.2 percent in 2006. The Public Expenditure Review (PER) has assessed Nicaragua's Public Financial Management (PFM) performance, using an international framework of reference that addresses seven critical dimensions: (i) credibility of the budget; (ii) comprehensiveness and transparency; (iii) budget planning; (iv) predictability and control in budget execution; (v) accounting, recording, and reporting; (vi) external scrutiny and audit; and (vii) donor practices that affect PFM. The assessment reveals that significant progress has been made since January 2004 in the implementation of the 2003 Country Financial Accountability Assessment (CFAA) Action Plan, but that some areas require further attention. Based on that assessment, the following measures are considered critical for scaling up ongoing efforts to reform and modernize public financial management (PFM). Nicaragua has come a long way since the beginning of this decade in bringing its overall fiscal balances under control. This puts Nicaragua in a good position for combating poverty in a sustained manner. To maintain that position, however, it will need to overcome further challenges that threaten to undermine fiscal stability in the medium term, notably a rapidly growing public wage bill and fiscal transfers to the municipalities. Looking beyond macroeconomic stability, Nicaragua also needs to pick up the pace of economic growth in order to generate greater momentum in poverty reduction. In this regard, the PER has identified various options for improving the quality of public expenditures in key areas relevant for economic growth. It also pointed out the most important measures needed to modernize public expenditure management and, thereby, facilitate the adjustments needed to improve the quality of public spending in a cost-effective manner. It is hoped that these insights prove useful to the authorities in their efforts to promote faster growth and poverty reduction in Nicaragua.